Review of The Kineros Model for Predicting The Effect of Land Use on The Surface Run-Off - Andi Setyo Pambudi (Indonesian Journal of Applied Research (IJAR), 2021)
Topics protection of catchment area relating to land use to support sustainability and environmental capacity is an interesting topic to be discussed scientifically. The increasing frequency of floods, droughts, landslides, and water crises are recently showed that the management of watersheds (DAS) has not been optimal. The Kineros Model for predicting the effect of land use on the surface run-off need to be improve in application. This paper has shown that the protection of natural ecosystems has a better impact than infrastructure development, especially about preventing inundation due to high surface runoff. This journal will strengthen the need for watershed-scale erosion prediction analysis because of its ability to define strategic areas of policy intervention to enable policymakers and the community to carry out recovery programs/activities more effectively and focused. The accuracy of determining the location of the policy has an impact on cost, time, and energy efficiency. Spatial calculation/analysis models combined with social and economic approaches will create a balanced and integrated sustainable development. The reviewer suggests a realistic combination of approaches, which combines the spatial aspects and technocratic calculations aspects of economic instruments that become balanced in a multidisciplinary concept.